2021
DOI: 10.3390/biom11121812
|View full text |Cite
|
Sign up to set email alerts
|

The Nuts and Bolts of SARS-CoV-2 Spike Receptor-Binding Domain Heterologous Expression

Abstract: COVID-19 is a highly infectious disease caused by a newly emerged coronavirus (SARS-CoV-2) that has rapidly progressed into a pandemic. This unprecedent emergency has stressed the significance of developing effective therapeutics to fight the current and future outbreaks. The receptor-binding domain (RBD) of the SARS-CoV-2 surface Spike protein is the main target for vaccines and represents a helpful “tool” to produce neutralizing antibodies or diagnostic kits. In this work, we provide a detailed characterizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…The usage of E. coli is often not recommended for challenging proteins that undergo glycosylation and require complex folding, such as the SARS-CoV-2 spike [ 64 , 65 ]. However, recent structural data from the circular dichroism and gel-filtration chromatography of the His-tagged recombinant SARS-CoV-2 spike proteins produced in E. coli and in mammalian HEK-293 cells evidenced that both of the proteins are stable and correctly folded, and capable of binding angiotensin-converting enzyme 2 (ACE2) [ 66 ]. Moreover, the functional data provided by ThermoFisher R&D also demonstrated that the E. coli recombinant SARS-CoV-2 spike (#RP-87668) efficiently recognised and bound ACE2 (proprietary data).…”
Section: Resultsmentioning
confidence: 99%
“…The usage of E. coli is often not recommended for challenging proteins that undergo glycosylation and require complex folding, such as the SARS-CoV-2 spike [ 64 , 65 ]. However, recent structural data from the circular dichroism and gel-filtration chromatography of the His-tagged recombinant SARS-CoV-2 spike proteins produced in E. coli and in mammalian HEK-293 cells evidenced that both of the proteins are stable and correctly folded, and capable of binding angiotensin-converting enzyme 2 (ACE2) [ 66 ]. Moreover, the functional data provided by ThermoFisher R&D also demonstrated that the E. coli recombinant SARS-CoV-2 spike (#RP-87668) efficiently recognised and bound ACE2 (proprietary data).…”
Section: Resultsmentioning
confidence: 99%
“…Spectra of the WT match those reported in the literature. [10] , [43] , [44] , [45] More importantly, none of the mutations caused significant changes in the spectra, implying that the Delta mutations do not affect the global protein structure.
Figure 2 (A) SDS-PAGE of purified RBD constructs.
…”
Section: Resultsmentioning
confidence: 98%
“…The findings suggest that the absence of glycosylation could partially affect ACE2 binding in vitro ( 52 ). In another study and in parallel with HEK-293 and insect cells, the E. coli -expressed RBD characterization showed the ability of the bacterial expression system in producing high-quality and antibody-recognizable proteins ( 53 ).…”
Section: Discussionmentioning
confidence: 99%